Implementation of Attractant Ratios to Attract Insects in the Clove Plant Ecosystem in West Langowan District, Minahasa - Deflly Ansye Shilfana Turang; Frangky H. Rorong; Robert W. Tairas (Postgraduate, University of Mataram, 2026)
The purpose of this study was to examine insects trapped using bioethanol-methanol attractant traps, examine the types of clove plant pests, natural enemies, detritivores, and pollinators, and calculate insect diversity in the clove plant ecosystem. The research was conducted in Manembo Village, West Langowan District. This study used a qualitative method with bioethanol-methanol traps as attractants to capture insects in the clove plantation ecosystem. The location was divided into two areas, and the attractant traps were placed randomly. The results showed that 12 orders were identified: Coleoptera, Diptera, Hymenoptera, Hemiptera, Blattodea, Orthoptera, Odonata, Neuroptera, Thysanoptera, Arachnida, and Acariformes. The population abundance at Location A was 1063 individuals, and at Location B, 748 individuals. The diversity analysis results showed that H' was still classified as moderate, which was influenced by the lack of a dominant family in clove plantations. The dominance index () indicated that no insects were highly dominant in clove plantations.